KAJIAN DETERMINAN KEBERLANGSUNGAN PRODUKSI TENUN GRINGSING DI DESA TENGANAN PAGRINGSINGAN KABUPATEN KARANGASEM - Defianti, Ni Putu Monita; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 8 (2020): VOL 9 NO 8, AGUSTUS 2020 (1631 - 1887), 2020)
This study aims to (1) analyze the simultaneous influence of labor, uniqueness, and capital on production, (2) analyze the partial effect of labor, uniqueness, and capital on production, and (3) analyze social capital in moderating the effect of partial labor, uniqueness, and capital to production. The data used are primary and secondary data, with a population of 155 weavers and a sample of 62 weavers in Tenganan Pagringsingan Village, Karangasem Regency. The sampling technique is random sampling with the help of the Random Number Generator (RNG) tool. The analysis technique used is Moderated Regression Analysis (MRA). The results showed that, labor, uniqueness, and capital simultaneously had a significant effect on production. Labor partially has a positive effect on production, uniqueness partially has a negative effect on production, and capital has a partially positive effect on production. Meanwhile, social capital strengthens the positive influence of labor on production, social capital weakens the negative influence of uniqueness on production, and social capital strengthens the positive influence of labor on production. Keywords : Labor, Uniqueness, Capital, Production, and Social Capital